Solar Tracker: Performance Analysis and Optimisation of Efficiency - Aneja, Preety; Bhateja, Pranshu (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 9 No 3&4 (2022): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2022)
Solar energy is one of the richest source of renewable energy on Earth, thus its harnessing is very much necessary for the useful conversion of light energy into electric energy. Solar panels are developed in this direction. Many scientists have developed various methods to gather the solar irradiation in order to maximize the extraction of electric power from the Photovoltaic generators. However, the problem with the solar power is that it is directly dependent on light intensity. The main hindrance with solar panels is their low efficiency with huge investment. Studies show that a solar panel converts 20-40% of energy incident on it to electrical energy. The solution is to use a tracking system1, 7 that maintains the panel’s position orthogonal with the light source. There are many tracking systems designs available including passive and active systems with one or two axes of freedom.8, 9 It has been found that the overall efficiency gain in single-axis solar tracker designed in10 is 27% than that of fixed mechanism. We had optimised the tracker efficiency by performing the experiment with solar tracker for consecutive three days and thus results were analysed by using statease software. Moreover, the testing showed that the power used by the tracking system was much less than that of power gained by tracking system. While working on the developed set-up, focus was given on the incremental efficiency of the solar power generation system. In the present work, further performance analysis is taken up with the help of various parameters viz. Specific Energy Production (SEP), Performance Ratio (PR), Ground Cover Ratio (GCR) and Surface Performance Ratio (SPR)11 to further elaborate the efficiency enhancement in solar trackers as compared to fixed systems. How to cite this article: Aneja P, Bhateja P. Solar Tracker: Performance Analysis and Optimisation of Efficiency. J Adv Res Alt Energ Env Eco 2022; 9(3&4): 1-9. DOI: https://doi.org//10.24321/2455.3093.202202